Redesign Tigaraksa City Forest Lake's Tourism Landscape in Tangerang Regency Using Sustainable Tourism Approach - Wistoro, Luthfie Adli; Hutriani, Ina Winiastuti; Franjaya, Eduwin Eko (Lakar: Jurnal Arsitektur, 2025)
Tigaraksa Urban Forest is a city forest located in the Tangerang Regency Government Center Area with an area of 8.5 hectares. Based on the Tangerang Regency RTRW 2011-2031, Tigaraksa Urban Forest is planned as a lake tourism area. And the Banten Province RIPPDA 2018-2025 has a vision of "Making Banten a World-Class Destination that is Competitive and Sustainable". Tigaraksa Urban Forest needs to be aligned with the Tangerang Regency RTRW and the Banten Province RIPPDA to make the city forest a lake tourism area with sustainable tourism. The objectives of the study (1) identify problems and potential redesign of the Tigaraksa Urban Forest landscape as a lake tourism area with a sustainable tourism approach in Tangerang Regency (2) provide recommendations for redesigning the Tigaraksa Urban Forest landscape as a lake tourism area with a sustainable tourism approach in Tangerang Regency. The research method uses a mixed method with design stages based on LaGro (2008). The results of the study (1) the physical landscape conditions of the city forest are quite suitable for lake tourism, (2) the socio-culture is suitable for both activities and regional regulations as lake tourism, (3) the concept of "TRISAKATARA" recommends city forests as sustainable lake tourism from environmental, socio cultural and economic aspects. The concept is applied to create city forests as sustainable lake tourism by paying attention to environmental, socio-cultural, and economic aspects with the output of site plans, enlargements, and 3D visualizations.